Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru - Sari, Nani Yulia (Yayasan Sembilan Pemuda Indonesia, 2025)
Principal leadership has a significant influence in improving teacher performance, which ultimately impacts the quality of education in schools. This study aims to analyze the role of principal leadership in supporting teacher performance through motivational strategies, supervision, and competency development. This study uses a descriptive qualitative method with data collection techniques in the form of interviews, observations, and documentation. The results of the study indicate that the principal acts as an active motivator, supervisor, and facilitator in improving the quality of teacher learning. The principal is able to create a conducive work climate through open communication, giving awards for teacher achievements, and training that supports their professional development. In addition, through planned supervision, the principal also provides constructive input and feedback to improve teacher performance. In conclusion, effective and adaptive principal leadership plays an important role in encouraging work enthusiasm, improving competency, and motivating teachers to give their best in the learning process. These findings underline the importance of quality leadership in improving the quality of education.